Integrated Strength and Fundamental Movement Skill Training in Children: A Pilot Study - Fay Grainger; Alison Innerd; Michael Graham; Matthew Wright (Children, 2020)
Competence in fundamental movement skills is essential to enable children to be physically active. We investigated the effect of an integrated fundamental movement skill with a strength training intervention on children’s fundamental movement skills. Seventy-two (53% female) 10- to 11-year-old children from three primary schools assented to take part in this study (87% compliance). Schools were randomly allocated to a control (no intervention; n = 21), fundamental movement skill (FMS) (n = 18) or FMS and strength (FMS+; n = 20) group. Interventions were delivered twice weekly for four weeks, in addition to normal physical education. FMS competence was measured through the Canadian agility and movement skills assessment (CAMSA) (product-process) and through countermovement jump (CMJ) and 40-m sprint tests (product). Improvements were observed in the CAMSA in both FMS (4.6, 95% confidence intervals 2.9 to 6.4 Arbitrary Units (AUs), second-generation p-value (pδ) = 0.03) and FMS+ (3.9, 2.1 to 5.3 AU, pδ = 0.28) with no difference beyond our minimum threshold of 3 AU observed between these intervention groups (pδ = 1). Clear improvements in CMJ were observed in FMS+ relative to the control (25, 18 to 32%, pδ = 0) and FMS groups (15, 6.1 to 24%, pδ = 0). These preliminary data suggest combined FMS and strength training warrants further investigation as a tool to develop fundamental movement skills in children.